And Now for Something Completely Different: Inattentional Blindness during a Monty Python's Flying Circus Sketch. (February 2015) - Wiseman, Richard; Watt, Caroline
Perceptual science has frequently benefited from studying illusions created outside of academia. Here, we describe a striking, but little-known, example of inattentional blindness from the British comedy series "Monty Python's Flying Circus." Viewers fail to attend to several highly incongruous characters in the sketch, despite these characters being clearly visible onscreen. The sketch has the potential to be a valuable research and teaching resource, as well as providing a vivid illustration of how people often fail to see something completely different.